Singlet oxygen mediated dual C–C and C–N bond cleavage in visible light. Issue 15 (2nd April 2020) - Ritu,; Sharma, Charu; Kumar, Sharvan; Jain, Nidhi
Abstract : A tandem cleavage of carbon–carbon and carbon–nitrogen bonds in imidazo[1, 2- a ]pyridines and imidazo[1, 2- a ]quinolines is reported in the presence of eosin Y and visible light. Abstract : A tandem cleavage of carbon–carbon and carbon–nitrogen bonds in imidazo[1, 2- a ]pyridines and imidazo[1, 2- a ]quinolines is reported in the presence of eosin Y and visible light. The ring opening occurs under ambient conditions through singlet oxygen insertion, bond cleavage and CO2 elimination, and produces N -(pyridin-2-yl) amides and N -(quinolin-2-yl) amides in high yields. The reaction shows good versatility, and does not require strong external oxidants and additives.